2005
DOI: 10.1093/carcin/bgi069
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of immortalized colorectal crypt cells by microcystin involving constitutive activation of Akt and MAPK cascade

Abstract: It has been shown by epidemiological and animal studies that microcystin is an important exogenous factor involved in the carcinogenesis of colorectal cancer (CRC). However, details of the mechanism remain unclear. Transformation of colorectal cells is an important initial step in carcinogenesis. Whether microcystin is capable of transforming immortalized colorectal crypt cells, and what the mechanism might be, was investigated. In the present study, we demonstrated that immortalized colorectal crypt cells cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 46 publications
5
37
0
1
Order By: Relevance
“…Since the transformation of colorectal cells is an important initial step in carcinogenesis (Zhu et al, 2005), these results support the hypothesis of MCLR being a risk factor of colorectal cancer (Zhou et al, 2002). In the same study, it was also demonstrated that members of the Ras and Raf families were activated, but without further activation of ERK1/2 kinases (Zhu et al, 2005). Here we found in Vero-E6 cells that low MCLR concentration affected the ERK1/2 but not the p38 and JNK MAPK pathways.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Since the transformation of colorectal cells is an important initial step in carcinogenesis (Zhu et al, 2005), these results support the hypothesis of MCLR being a risk factor of colorectal cancer (Zhou et al, 2002). In the same study, it was also demonstrated that members of the Ras and Raf families were activated, but without further activation of ERK1/2 kinases (Zhu et al, 2005). Here we found in Vero-E6 cells that low MCLR concentration affected the ERK1/2 but not the p38 and JNK MAPK pathways.…”
Section: Discussionsupporting
confidence: 80%
“…A study from Zhu et al (2005) demonstrated that MCLR (0.1 nM) is able to transform immortalized colorectal crypt cells (NCC), rendering them anchorage independent and highly proliferative through the activation of the Akt and the p38 and JNK MAPK pathways. Since the transformation of colorectal cells is an important initial step in carcinogenesis (Zhu et al, 2005), these results support the hypothesis of MCLR being a risk factor of colorectal cancer (Zhou et al, 2002). In the same study, it was also demonstrated that members of the Ras and Raf families were activated, but without further activation of ERK1/2 kinases (Zhu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports suggest that MCs modulate PPs activity not only by the direct inhibition of enzyme activity, but also through the regulation of protein expression [16][17][18][19][94][95][96][97]. PP1 and PP2A inhibition induces the disruption of the dynamic equilibrium of protein phosphorylation/dephosphorylation, leading to the damage of numerous cellular processes such as cytoskeleton organization, Wnt, Akt, p38, c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase 1/2 (ERK1/2) of mitogen-activated protein kinase (MAPK) signaling pathways, metabolism and cell cycle [20,[98][99][100][101] (Fig. 4).…”
Section: Modulation Of Pp1 and Pp2a Activitiesmentioning
confidence: 99%